Invasiveness of alien vascular plants in six arid zones of Europe, Africa and America - Sanz Elorza, Mario; González Bernardo, Francisco; Serreta Oliván, Alfredo; Gavilán Iglesias, Laura P. (Lazaroa, 2011)
Biological invasions are one of the most important components of global change, and have increasing effects on the loss of biodiversity and on human societies as a whole. The difficulties of accurately predicting the fate of a given introduction has led to increased interest in identifying situations where the risk posed by invaders is particularly high. We analyse patterns of plant invasions in arid zones to develop explicit invasion risk protocols. The study zones are five arid regions in three continents: the Mojave and Sonoran Deserts in North America, the Atacama Desert in South America, the Sahara in northern Africa and the Tabernas and Monegros in southwest Europe, (Spain). We test which life-history traits are related to invasiveness in these areas. We use Generalized Linear Mixed Models (GLMM) to model variation between species in invasion success as a function of eight predictors, potentially related to invasiveness: clonality, pollination model, dispersal syndrome, linking to moist soils, seed size, linking to disturbed habitats, salinity tolerance and longevity. We also analyse the differences that exist between the total alien flora in these six areas of the world with respect to the attributes that were considered. From the species perspective, when taxonomic effects were accounted for, only dispersal syndrome and linking to disturbed habitats appeared to be related to the invasive nature of plants. However, if taxonomic effects are not taken into account the variable salinity tolerance is also significantly related. In spite of the fact that the regions have important climatic analogies, there does not appear to be a clear general pattern in the attributes of alien flora, as these are largely dependent on local conditions.